Child mental health: Impact of introducing earlier compulsory school grades - Anna Linder; Ulf-G. Gerdtham; Gawain Heckley (Lund University, School of Economics and Management, Department of Economics, 2023)
The prevalence of mental ill-health is increasing among young people in many developed countries, raising concerns about their well-being. Experts have pointed to several potential contributing factors, including a heightened emphasis on educational achievement and performance evaluation, as well as shifting demands in the high-skilled job market. In this paper, we study the effect of introducing earlier grades in compulsory school on child mental health in Sweden. To do so, we exploit a grading reform in Swedish compulsory schools in which grades were introduced at an earlier age, in 6th grade instead of 8th grade as was previously the case. The reform provides a situation where the age at which children receive their first grade is arbitrary depending on if the child is born before or after the year-end. We show that girls who are exposed to one year earlier grades are more likely to be diagnosed with depression or anxiety by the end of compulsory school, controlling for potential age effects in a difference-in-discontinuities setup. We do not find similar effects among boys. Overall, these results imply that girls' mental well-being may be particularly responsive to educational assessment through grades at earlier ages.
Keywords: I10; I21; I28; 330; education policy; school grades; mental health; human capital development